Capital Taxes, the Redistribution of Wealth and Individual Savings - Atkinson, A. B. (Review of Economic Studies, 1971)
Journal Article Capital Taxes, the Redistribution of Wealth and Individual Savings Get access A. B. Atkinson A. B. Atkinson St John's College, Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 38, Issue 2, April 1971, Pages 209–227, https://doi.org/10.2307/2296780 Published: 01 April 1971